(untitled) (Международный научный журнал «Инженер», 2026)
This paper examines the architecture of a railcar monitoring system that employs Bluetooth Low Energy (BLE) beacons attached to railcars and gateways equipped with cellular connectivity (GSM, LTE, NB-IoT). A comparative assessment of existing tracking technologies (GPS, RFID, LoRa, etc.) is presented and the rationale for selecting a hybrid BLE + cellular approach is given. The network topology is described (star topology: BLE beacon → gateway → cloud), together with the hardware components (BLE beacons and cellular gateways) and the server infrastructure (MQTT, REST API, buffering, fault tolerance). Options for gateway placement at stations and in depots are considered, operational scenarios (in depot, at station, in transit) are analyzed, and the advantages and limitations of the proposed scheme are discussed. Examples of real-world solutions and technical data are provided.